Elaboration of garlic and salt spice with reduced sodium intake - RODRIGUES,JÉSSICA F. (2014)
Garlic and salt spice is widely used in Brazilian cookery, but it has a high sodium content; as high sodium intake has been strongly correlated to the incidence of chronic diseases. This study aimed to develop a garlic and salt spice with reduced sodium intake. Sensory evaluation was conducted by applying the spices to cooked rice. First, the optimal concentration of spice added during rice preparation was determined. Subsequently, seasonings (3:1) were prepared containing 0%, 50% and 25% less NaCl using a mixture of salts consisting of KCl and monosodium glutamate; a seasoning with a 0% NaCl reduction was established as a control. Three formulations of rice with different spices were assessed according to sensory testing acceptance, time-intensity and temporal domain of sensations. The proportions of salts used in the garlic and salt spice did not generate a strange or bad taste in the products; instead, the mixtures were less salty. However, the seasonings with lower sodium levels (F2 and F3) were better accepted in comparison to the traditional seasoning (F1). Therefore, a mixture of NaCl, KCl and monosodium glutamate is a viable alternative to develop a garlic and salt spice with reduced sodium intake.